2015
DOI: 10.1108/jd-08-2013-0104
|View full text |Cite
|
Sign up to set email alerts
|

Domain knowledge and data quality perceptions in genome curation work

Abstract: Purpose -The purpose of this paper is to understand genomics scientists' perceptions in data quality assurances based on their domain knowledge. Design/methodology/approach -The study used a survey method to collect responses from 149 genomics scientists grouped by domain knowledge. They ranked the top-five quality criteria based on hypothetical curation scenarios. The results were compared using χ 2 test. Findings -Scientists with domain knowledge of biology, bioinformatics, and computational science did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
(116 reference statements)
1
4
0
Order By: Relevance
“…They argue that this is important for determining the accuracy and currency of data. These definitions align with other definitions of provenance as traceability (Huang, 2015; Wang and Strong, 1996).…”
Section: Literature Reviewsupporting
confidence: 76%
“…They argue that this is important for determining the accuracy and currency of data. These definitions align with other definitions of provenance as traceability (Huang, 2015; Wang and Strong, 1996).…”
Section: Literature Reviewsupporting
confidence: 76%
“…When assessing the relevance of data, earthquake engineers judged whether the data could be used to validate their models (Faniel and Jacobsen, 2010). Likewise, genomic scientists' used data relevance as one of the constructs they ranked highly in data selection (Huang et al , 2012; Huang, 2015). To assess alignment with research questions or aims, researchers have also shown how social scientists considered various aspects of data, such as topic and type of analyses they wanted to complete in order to evaluate whether the data were fit for their purposes (Curty, 2016; Sun and Khoo, 2017; Yoon, 2016b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…3.1.4 Domain knowledge and performance. Domain knowledge is defined as the degree of familiarity with a particular subject area (Huang, 2015). The domain knowledge of scientists has an impact on their information-seeking behavior, information systems implementation and decision-making (Wu et al, 2012;Vibert et al, 2014).…”
Section: Social Value Orientationmentioning
confidence: 99%